Evolution of natural product biosynthesis in the bicyclo[2.2.2]diazaoctane containing fungal indole alkaloids - Fraley, Amy E. (FEBS J, 2020)
The class of fungal indole alkaloids containing the bicyclo[2.2.2]diazaoctane ring is comprised of diverse molecules that display a range of biological activities. While much interest has been garnered due to their therapeutic potential, this class of molecules also displays unique chemical functionality, making them intriguing synthetic targets. Many elegant and intricate total syntheses have been developed to generate these alkaloids, but the selectivity required to produce these structures with high yield presents great barriers. Alternatively, if we can understand the molecular mechanisms behind how fungi make these complex molecules, we can leverage the power of nature to perform these chemical transformations. Here, we describe the various studies regarding the evolutionary development of enzymes involved in fungal indole alkaloid biosynthesis.